Nitrogen Fixing Bacteria and Their Application for Heavy Metal Removal: A Mini Review (Journal of Biochemistry, Microbiology and Biotechnology, 2021)
Nitrogen is a critical component of biological systems and typically serves as a constraint on production in both aquatic and terrestrial environments, although its shortage has been compensated for through the process of biological nitrogen fixation. Nitrogen fixation is a critical microbial activity that utilises nitrogenase enzymes to convert dinitrogen (N2) gas to ammonia (NH3). It is carried out by a diverse spectrum of bacteria known as nitrogen fixing bacteria. These include free-living bacteria such as Azotobacter, Bacillus, Beijerickia, and Clostridium, associative bacteria such as Azospirillum, Enterobacter, and Pseudomonas, and bacteria that form symbiotic associations with legumes such as Rhizobium and actinorrhizal plants such as Frankia. These bacteria contribute significantly to plant growth by producing phytohormones (such as auxins, cytokinins, gibberelins, and indole acetic acid), reducing the incidence of plant diseases through the production of siderophores and cell wall degrading enzymes, and increasing phosphorus nutrition via phosphate solubilization. Additionally, they remove heavy metal ions from solutions through a process called biosorption, which is a feasible, natural, environmentally benign, and economically viable technique of remediating heavy metal-contaminated environments.
Keywords: Nitrogen fixing bacteria; Plant growth promotion; Biosorption; Phytohormones; Heavy metals